Dispersion Stability of Carbon Nanotubes and Their Impact on Energy Storage Devices - Choi, Chunghyeon; Yun, Tae Gwang; Hwang, Byungil (Inorganics, 2023)
Carbon nanotubes (CNTs), with their extraordinary combination of mechanical, electrical, and thermal properties, have emerged as a revolutionary class of nanomaterials with immense potential in energy storage and harvesting devices. Realizing this potential hinges on a fundamental challenge: the dispersion stability of CNTs within various matrices. This review paper provides a comprehensive exploration of the critical interplay between CNT dispersion stability and its far-reaching implications for the performance of energy storage and harvesting technologies. By delving into the underlying mechanisms of dispersion, the strategies to achieve stability, and the direct effects on device functionality, this review sheds light on the intricate relationship between nanotube dispersion and the advancement of energy-related applications.
Keywords: batteries; carbon nanotubes; dispersion stability; energy harvesting devices; energy storage devices; supercapacitors